BEBERAPA FAKTOR YANG MENGHAMBAT AKSESIBILITAS MASYARAKAT MENGIKUTI PENDIDIKAN DI UNIVERSITAS UDAYANA - Sudibia, I Ketut; Windia, I Wayan; Bendesa, I Komang Gde; Tisnawati, Ni Made (PIRAMIDA, 2012)
One of the most important factors to improve the population quality is education.Udayana University is one of the oldest higher educations in Bali. The students are notonly coming from Bali, nor outside of Bali but also from overseas. The total of activestudents attending the education in Udayana University is 17.461. The recent data, fromthe last three years showed that there has been a quality improvement in terms ofeducation. This is proved by the tendency of improving Achievement Index Cumulative(IPK) for regular S1 as 3.05 in 2005, became 3.06 in 2006 and 3,14 in 2007.Apart from the success being mentioned above, Udayana University is still facingimportant problem related to the opportunity which is not taken by the student candidatesIt can be recorded that such opportunity (empty chair) in Unud is still very high (41%)although there was a declining number comparing to the last year data. Considering thefact that the number of SMU (high school) graduates tended to be high, it is importantto conduct research in order to find out the various factors slowing down the societyaccessibility to attend education in Udayana UniversityThe aims of this research are to find out the factors slowing down of the societyaccessibility to attend education in Udayana University. This research was conducted inthree outside cities of Bali, namely: Malang, Surabaya and Yogyakarta. These three citieswere chosen due to be that they have been known as the centers of education cities. Byconducting research outside of Bali, it is expected to find out that there are realisticreasons why they did not choose Udayana University as the place to continue theireducation. The respondents from each city are (1) 80 persons in Yogyakarta; (2) 70persons in Surabaya and (3) 70 persons in MalangThe influencing factors are viewed from the culture system study, among others :mind-set system, social and artifact aspects. The respondents generally stated the basicconsiderations why they did not choose Unud are (i) education quality (41.4%); (ii)education cost (9.1%); (iii) supporting facilities (10.9%); (iv) working prospects (24.5%)and (v) academic atmosphere (14.1%)In relation to such finding, the main suggestions to be implemented that Unudshould soon improve the education quality. The main key to improve the education isto qualify the teaching staff. The teaching-learning process done by all of UdayanaUniversity teaching staff must be thoroughly controlled, based upon the providedstandard operational procedure
Keywords: Education in Unud; Accessibility, Culture Study